Multiple Environmental Stresses and Broiler Internal Organs Somatic Indices under Controlled Environment - Ahmed, Zakia A.M.; El-Ghamdi, Zahraa H. (International Journal of Poultry Science, 2008)
The current trial is designed to investigate the effect of multiple environmental stresses (Heat, ammonia exposures and stocking density) on broiler’s organs somatic indices (SI) of liver, spleen and bursa fabricious under controlled environment (1-42 DO) during summer. Control birds: Bursa fabricus (Bf) index showed higher values from 1st -3rd wks. The minimum values for spleen and Bf indices were at 5th week old. Food conversion rate (FCR) was 1.8±0.56. Indoor ambient temperature (Ta.oC) is positively correlated with liver index Heat stressed body temperature (Tb.oC) is increased and be indicative to early stress (1st 4 hours exposure to 41oC) but chronic stress enforced bird acclimation and decreased final B wt/g. Liver and spleen indices were decreased while Bf index increased. The dramatic effects of expected generated ammonia under field can be modulated by allowing recovery period for elimination, where here it accompanied with non significant increased Tb but decreased final B.wt and SI of liver and spleen except the increased Bf index. Stocking density decreased final B wt and increased Tb but not affected birds SI. Conclusively persistence of some stresses enforced birds to habituate especially when be mild, at non critical early age (growth easily compensated), beside the controllable indoor climatic conditions in closed house during summer, all could alleviate the impact of intrinsic or extrinsic multiple stresses on broiler performance. The lymph organ (Bf) index was increased post heat and ammonia stress and not badly affected by stocking 17 bird/m2.